Implementing criteria-led discharge for acute admissions to facilitate the elective recovery from COVID-19: an example in acute tonsillitis - Huw Jones; Callum Findlay; Wei Chern Gavin Fong; Simon Goldie (BMJ Open Quality, 2023)
Background Healthcare systems face unprecedented numbers of patients waiting for elective treatments in the wake of the COVID-19 pandemic. Hospitals must urgently optimise patient pathways and build capacity to meet the populations health needs. Criteria-led discharge (CLD) is frequently used to optimise elective care pathways but may hold potential in discharging patients at the end of an acute hospital admission.Methods We conducted a quality improvement project to design and introduce a novel inpatient pathway using CLD for patients with severe acute tonsillitis. Our analysis compared the standardisation of treatment, length of stay, discharge time and readmission rate between those treated on the novel pathway compared with standard treatment.Results The study population included 137 patients admitted to a tertiary centre with acute tonsillitis. Introduction of the tonsillitis pathway using CLD resulted in a significant reduction in median length of stay from 24 hours to 18 hours. Of those treated on the tonsillitis pathway, 52.2% were discharged prior to midday compared with 29.1% who received standard treatment. No patient discharged using CLD required readmission.Conclusion CLD is safe and effective at reducing length of stay in patients requiring acute hospital admission for acute tonsillitis. CLD should be used and evaluated in further novel patient pathways across different areas of medicine to optimise care and build capacity for provision of elective healthcare services. Further research is required to investigate safe and optimal criteria which indicate patients are fit for discharge.